The Study on History of Photomontage and the Efficiency of Art Schools on it - Dianat, Fereshteh (Journal of History Culture and Art Research, 2017)
Photomontage is a combination of several shots joined together for artistic effect or to show more of the subject than can be shown in a single artwork. Images were composed by cutting, gluing, arranging and overlapping two or more photos or reproductions of photos together, sometimes in combination with other non-photographic material such as text or other abstract shapes. The process of creating a collage photo can be traced back to the first darkroom printing attempts, when photographers experimented with direct contact printing of objects placed on photographic plates, or techniques such as double exposure and masking. Manipulation has a long history exactly as long as history of photography. With invention of photography, photomontage played an important role. It is interesting to say that also many years has passes that time, it is important as much as before. The question in this article is searching on the importance of photomontage and the important effect of other art schools on it. It is tired to conclude that with the invention of photography, photomontage was emerged and it was depended on photography. Moreover, the emergence of other art schools as Dadaism has had a positive effect on photomontage as well. This article is about the history of photomontage and the efficiency of other art schools like Dadaism on it.